Guarantee As an Appropriate Solution for Dealing with Possible Breach of Contract - Meysam akbari dehno; morteza shshbazinia; Mohammad Bagher Parsapour (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2014)
In order to ensure a timely performance of contractual obligation, the use of guarantee is regarded as one of the most appropriate ways of dealing with a breach of promise. Compared to the Convention on the International Sale of goods, it is difficult to find a legal basis for a possible breach in national law. Nevertheless, in a substantial number of cases in Iranian law, by considering the theory of possible breach, guarantee has been used to address the possible breach of promise by promisor. Until this legal gap is filled, it would appear that it is appropriate to use the principle of demand guarantee for the purpose of securing the performance of contractual obligations in domestic law.